2012
DOI: 10.1262/jrd.11-128t
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Localization of NO Synthase Isoenzymes (iNOS and eNOS) in Development of the Rabbit Placenta

Abstract: Abstract. Nitric oxide synthase (NOS) is a key regulator of angiogenesis and embryogenesis in the mammalian reproductive process. Here, we attempted to clarify the expression and localization of inducible and endothelial NOS (iNOS and eNOS) in the developing rabbit placenta. Real-time RT-PCR analysis indicated that iNOS mRNA was significantly upregulated till the complete development of the placenta (d18), and then significantly decreased at the end of fetal growth stage (d28) during successful pregnancy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Other positive result obtained in the current study was that pregnant animals fed enriched diet showed increased plasma progesterone concentrations at 7 and 14 days of pregnancy. In this period, embryo implantation and immediately placenta formation occur (Khan et al, 2012), therefore, the higher the progesterone concentrations, the better implantation and placentation process would take place, with an improved survival post-implantation of foetuses (Froment et al, 2006). In this regard, similar progesterone results have been obtained in previous work (Rebollar et al, 2014) at 7 days of pregnancy and in additional trials with the same supplement (Rodríguez et al, 2016) we have observed more born alive in enriched does.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Other positive result obtained in the current study was that pregnant animals fed enriched diet showed increased plasma progesterone concentrations at 7 and 14 days of pregnancy. In this period, embryo implantation and immediately placenta formation occur (Khan et al, 2012), therefore, the higher the progesterone concentrations, the better implantation and placentation process would take place, with an improved survival post-implantation of foetuses (Froment et al, 2006). In this regard, similar progesterone results have been obtained in previous work (Rebollar et al, 2014) at 7 days of pregnancy and in additional trials with the same supplement (Rodríguez et al, 2016) we have observed more born alive in enriched does.…”
Section: Discussionsupporting
confidence: 87%
“…Nonetheless, although there were no differences in the weight of neonates, PUFA supplementation had a favourable effect on the individual kits body size. That was evident the day of parturition, probably due to the higher plasma progesterone concentration when placenta formation occurs (Khan et al, 2012). In this connection, several evidences from animals and humans suggest that the dietary n-3 PUFA during pregnancy promotes early neural and retinal tissues development and regulates behavioural and neurochemical aspects related to stress responses, growth and cognitive functions, being very important in order to vitality of newborns (Bernardi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…has a high expression level of NOS, especially NOS3 (Khan et al 2012), which may facilitate sildenafil citrate function. Both processes would be expected to stimulate neoangiogenesis and may also improve maternal blood flow to the placenta, thereby facilitating nutrient and oxygen delivery to the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, lipid peroxides and oxygen radicals can alter endothelial cells, resulting in fibrin deposition in the vessel walls [67]. Consequently, the arterial sinuses system in the rabbit, which can be identified within this period of gestation [78] and is responsible to retain maternal blood flow and then supply it to fetal area could be altered, resulting in IUGR. On the other hand, the reduction in decidua size could be a mechanism of these placentas to support fetal demands for growth by depletion of their glycogen reserves allocated in the small uninucleated cells of this placental section [79], and therefore may explain the increase in placental efficiency and the reduction in weight.…”
Section: Discussionmentioning
confidence: 99%